'A Plague of Salaried Marxists': Sexuality and Subsistence in the Revolutionary Imaginary of Concha Michel. (October 2017) - Olcott, Jocelyn
This article examines work of Mexican singer and activist Concha Michel, particularly the pamphlet Marxistas y 'marxistas' that sealed her expulsion from the Mexican Communist Party (Partido Comunista de México, PCM). Michel wrote the pamphlet after her return from the Soviet Union, where her experiences only confirmed her belief that revolutionary governments in Mexico and the Soviet Union alike had failed to attend to the massive amounts of social and cultural labor performed overwhelmingly by women. In particular, Communists' emphasis on modernization and scientific theory privileged the 'social economy' of commodified production and devalued what she dubbed the 'natural economy' of subsistence, reproduction, and artistic labors. The pamphlet draws parallels with the capitalist exploitation of laborers and the sexual exploitation of women perpetrated even by Communist Party leaders. Michel's refusal to submit to the Party line resulted in her high-profile expulsion from the party, a fate that befell much of her social circle. Over subsequent decades, however, her commitment to activism on behalf of women, celebration of Mexico's indigenous cultures, and persistent critique of the elision of subsistence labors would earn her celebrity among Mexican maternalist feminists.